Overview of Ankle Brachial Index (ABI) Values on Diabetes Mellitus Type 2 in Blitar - Ulfa Husnul Fata (STIKes Patria Husada Blitar, 2017)
Examination of foot vascularization often used for patients with DM who have Perypheral Arterial Disease (PAD) is to measure the value of Ankle Brachial Index (ABI). ABI examination is a non-invasive gold standard measurement to detect vascular disorders of the peripheral arteries and is recommended as part of the assessment process to help formulate the diagnosis in at-risk individuals. The purpose of this study is to provide an overview of the value of ABI in people with diabetes mellitus type 2 in Village ofKepanjenKidul and Village KarangsariBlitar City. The method in this research is descriptive with respondent of type 2 diabetes mellitus which counted 32 respondents. Methods of data collection with check list and ABI score. The results of this study indicate that the value of ABI in people with type 2 diabetes with ABI value right and left extremities borderline and abnormal categories at most are female gender, abnormal value many in diabetics who do not routinely consume anti diabetic drugs, abnormal ABI value many in patients who do not exercise regularly, abnormally abnormal ABI values in patients who have never performed foot therapy, and abnormal ABI values are many in patients who do not implement the diet. Therefore, foot examination is very important to be done regularly to reduce the risk of foot ulcers in patients with diabetes mellitus.